δ- and β-cells are electrically coupled and regulate α-cell activity via somatostatin - Briant, L; Reinbothe, T; Spiliotis, I; Miranda, C; Rodriguez, B; Rorsman, O (Wiley, 2017)
Glucagon, the body’s principal hyperglycaemic hormone, is released from the α-cells of the pancreatic islet. The secretion of this hormone is dysregulated in type 2 diabetes mellitus but the mechanisms controlling secretion are not well understood. Regulation of glucagon secretion by factors secreted by neighbouring β- and δ-cells (paracrine regulation) have been proposed to be important. In this study, we explored the importance of paracrine regulation by using an optogenetic strategy. Specific light-induced activation of β-cells in mouse islets expressing the light-gated channelrhodopsin-2 resulted in stimulation of electrical activity in δ-cells but suppression of α-cell activity. The activation of the δ-cells was rapid and sensitive to the gap junction inhibitor carbenoxolone, whereas the effect on electrical activity in α-cells was blocked by CYN 154806, an antagonist of the somatostatin-2 receptor. These observations indicate that optogenetic activation of the β-cells propagates to the δ-cells via gap junctions, and the consequential stimulation of somatostatin secretion inhibits α-cell electrical activity by a paracrine mechanism. To explore whether this pathway is important for regulating α-cell activity and glucagon secretion in human islets, we constructed computational models of human islets. These models had detailed architectures based on human islets and consisted of a collection of >500 α-, β- and δ-cells. Simulations of these models revealed that this gap junctional/paracrine mechanism accounts for up to 23% of the suppression of glucagon secretion by high glucose.